A influência dos conceitos em nossas percepções: um diálogo entre a filosofia e a psicologia experimental - Vollino, Maurício da Rosa (Universidade do Vale do Rio dos Sinos, 2023)
In this dissertation, I reflect on the interaction between concepts and perception to answer the question “do the concepts influence how we perceive the world?”. This research is inspired by the results of empirical studies involving attention and language in colors perception, in special orientation and in activities with orientation of selective attention. That is, the object of study here is the relation between attention, language and conscious perception which expose that attention is necessary for conscious perception to arise. Because of the orientation of selective attention in some experiment occurs the phenomenon known as inattentional blindness. Some unexpected stimuli in the visual field are not attended when subjects are attending to an activity. Therefore, the unexpected stimuli are not perceived consciously. Hence, attention is necessary for consciousness, and it defines which stimuli are consciously perceived showing that there is a hierarchy in relation to which selected stimuli would be conscious perceived. This shows the relevance of importance of the stimuli to the subject, which depends on the context, relevance, semantic familiarity, or expectation. On this view, attention owns the roll of select which information are conscious perceived. As consequence of orienting the selective attention in some experiments occurs the phenomenon called Inattentional Blindness. In order to observe the behavior of attention and inattentional blindness it will be studied the conceptual elements that interact with those cognitive phenomena. I want to understand, by the point of view of philosophy of language and philosophy of mind, the cognitive mechanisms behind the use of language or, more specifically, behind the use of concepts using empiric experiments from cognitive sciences as example of interaction between concepts, attention, and conscious perception. According to linguistics, language is a guide to attention, and attention is necessary to conscious perception to arise. About the elements of language, it is worked here the conceptual elements which make possible the attraction of attention and as stated in this work are responsible in making a stimulus sufficiently important to attract attention. About the study of concepts in Philosophy history, many theories arrived trying to explain the behavior of concepts, such as Classical Theory, Prototype Theory, Informational Atomism Theory. Here, I adopt the conceptual theory developed by Jesse Prinz called Proxytype Theory which envelopes successful tools of previous theories of concepts. According to the theory all concepts are copy of combinations or copies of perceptual representations originated in neural circuits with perceptual or motor functions and the mental process are affected by perceptual characteristics. Finally, once understood the conceptual tools of Prinz’s theory of concepts I answer the question “Do concepts influence the way we perceive the world?” by resuming at the end of this work the experiments described throughout this dissertation. Attention interacts with conscious perception and, as I expose in here, concepts are capable of attract attention by intentional contents and cognitive contents. Due to these factors, attention is oriented and inattentional blindness may occur, reinforcing the thesis that attention is necessary for consciousness.
Keywords: Atenção; Filosofia da mente; Conceitos; Consciência perceptual; Linguagem; Attention; Philosophy of mind; Concepts; Perceptual consciousnes; Language; ACCNPQ::Ciências Humanas::Filosofia